1997
DOI: 10.1146/annurev.med.48.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis Caused by Hacek Microorganisms

Abstract: The HACEK group of fastidious gram-negative organisms is a recognized but unusual cause of infective endocarditis, responsible for approximately 3% of cases. We report our experience with 45 cases of endocarditis caused by HACEK organisms. In Olmsted County, Minnesota, the incidence of HACEK endocarditis was 0.14 per 100,000 person-years. In patients with native valves, 33 cases occurred, and in patients with prosthetic valves, 12 cases occurred. The most common presenting symptoms were fever, splenomegaly, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(57 citation statements)
references
References 11 publications
1
54
0
2
Order By: Relevance
“…The three species A. actinomycetemcomitans, A. aphrophilus, and A. segnis are the second most common cause of HACEK endocarditis, found in 26 (34%) of the 77 cases of HACEK endocarditis enrolled within the ICE prospective cohort study [7], and 16 out of 45 (36%) cases of HACEK endocarditis reported from the Mayo Clinic [2]. The association between Aggregatibacter spp.…”
Section: Aggregatibacter Sppmentioning
confidence: 97%
See 3 more Smart Citations
“…The three species A. actinomycetemcomitans, A. aphrophilus, and A. segnis are the second most common cause of HACEK endocarditis, found in 26 (34%) of the 77 cases of HACEK endocarditis enrolled within the ICE prospective cohort study [7], and 16 out of 45 (36%) cases of HACEK endocarditis reported from the Mayo Clinic [2]. The association between Aggregatibacter spp.…”
Section: Aggregatibacter Sppmentioning
confidence: 97%
“…parainfluenzae is the most common cause of HACEK endocarditis, found in 28 (36%) of the 77 cases of HACEK endocarditis enrolled within the International Collaboration on Endocarditis (ICE) prospective cohort study during years 2000-2006 [7], and 12 out of 45 (27%) cases of HACEK IE reported from the Mayo Clinic in Rochester, during years 1970-1992 [2]. The association between H. parainfluenzae bacteremia and IE is strong, with a positive predictive value (PPV) for the diagnosis of IE estimated at 55% (10/18) [4].…”
Section: Haemophilus Parainfluenzaementioning
confidence: 99%
See 2 more Smart Citations
“…The so-called HACEK group of fastidious Gram-negative organisms is a recognized but unusual cause of infective endocarditis, responsible for 1.4 to 3% of cases (209,210). The group was originally described to encompass Haemophilus species, Actinobacillus actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, and Kingella kingae (211).…”
Section: Infectious Endocarditis and The Hacek Groupmentioning
confidence: 99%